2016
DOI: 10.1590/1413-70542016406048415
|View full text |Cite
|
Sign up to set email alerts
|

Farming and soil urban occupation in the water quality of Jaboticabal and Cerradinho streams

Abstract: Since the end of the twentieth century, 100% of the urban sewage from the city of Jaboticabal has been collected by interceptors and routed to a treatment plant. Between 1999 and 2000, studies on the effect of this environmental care showed that it did not efficiently clean up the water from the two streams that run through the city and flow into an agricultural area. This paper focuses on assessing the influence of soil use on the water quality of surface waters from these two streams. The study was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The WQICETESB was not significant, however, when correlated directly with the variables that compose it; we found a significant relation of agricultural culture with pH and TC (rPearson = (+) 0.99; p < 0.01). This association demonstrates coherence, considering the loss of soil nutrients and organisms (Silveira et al, 2016), as observed in Point 1, the only site presenting such a category, with values of 15% ( Figure 1C). All the other variables showed trends to the expected (that riparian's forest reduction decrease the water quality), but did not show significance for this level of probability.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…The WQICETESB was not significant, however, when correlated directly with the variables that compose it; we found a significant relation of agricultural culture with pH and TC (rPearson = (+) 0.99; p < 0.01). This association demonstrates coherence, considering the loss of soil nutrients and organisms (Silveira et al, 2016), as observed in Point 1, the only site presenting such a category, with values of 15% ( Figure 1C). All the other variables showed trends to the expected (that riparian's forest reduction decrease the water quality), but did not show significance for this level of probability.…”
Section: Resultsmentioning
confidence: 54%
“…Moreover, their environmental function is to safeguard water resources, landscape, geology, soil and local biodiversity, besides offering sustenance and well-being to human populations (Brasil et al, 2009). Thus, if water quality is the result of a series of natural phenomena occurring in a watershed, it can reasonably be considered that the way man changes these natural systems, uses and occupies the land, has a direct impact on water quality (WHO, 2004;Silveira et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Water with high acidity generally stimulates the corrosive potential of the medium [7]. Finally, electrical conductivity refers to the ability of water to transmit electrical current, which results from the presence of cations and anions formed by the dissociation of other substances [8].…”
Section: Introductionmentioning
confidence: 99%
“…The ponds used in the present study were constructed on eutroferric latosols (density ≈ 1.5 g/cm 3 ), which have a high capacity to adsorb organic material, and quickly become anoxic upon being saturated with water (Amorim and Batalha, ; Silveira et al, ; Levinski‐Huf & Klein, ). These ponds have been used for over 20 years and as such, the bottom soils have incorporated high quantities of organic nitrogen from the sinking feed and feces of the farmed organisms as demonstrated by the high pre‐flood nitrogen concentration of the soil (~2.5–4.0 g N/kg).…”
Section: Discussionmentioning
confidence: 99%